The theoretical association between behavioral economics and investment decisions in Keynes - Casonato, Lucas; Venson, Auberth Henrik; Sbicca, Adriana (Brazilian Keynesian Review, 2021)
The article explores the relationship between the investment decision in Keynes and research in Behavioral Economics. For the identification of common theoretical elements between these two approaches, their contributions were briefly recovered from the history of economic thought. The developed discussion contrasts elements that support the two currents of thought, promoting a reading of their complementary theoretical aspects: (i) rationality and uncertainty; (ii) heuristics and conventions; (iii) individual decision and investment decision. This allows a deeper understanding of these proposals, and a better understanding about: (1) the role of subjectivity in Behavioral Economics from using the concept of heuristics in the analysis of the Keynes» investment decision; and (2) the psychological aspects pointed out by Keynes that explain how elements that influence the investment decision (interest rate, for example), are not determinants in choices. The work supports a complementarity of Prospect Theory and Mental Accounting with the psychological analysis of aspects pointed out by Keynes as fundamental in the investment decision: animal spirit, expected return and interest rate, fundamental uncertainty and the relationship between marginal capital efficiency and interest rate.